Answer:
4
Step-by-step explanation:
The answer is 1952 because you have to add all of the numbers together
If you would like to solve - 3 * a^2 - b^3 + 3 * c^2 - 2 * b^3, if a = 2, b = -1, c = 3, you can calculate this using the following steps:
a = 2, b = -1, c = 3
- 3 * a^2 - b^3 + 3 * c^2 - 2 * b^3 = - 3 * 2^2 - (-1)^3 + 3 * 3^2 - 2 * (-1)^3 = - 3 * 4 - (-1) + 3 * 9 - 2 * (-1) = - 12 + 1 + 27 + 2 = 18
The correct result would be 18.
Answer:
it looks decent just give it make it more detailed otherwise it looks good
2/9 divided by 1/2. invert the second fraction and multiply
2/9 * 2/1 = 4/9